Visual acuity and contrast sensitivity following Descemet stripping automated endothelial keratoplasty. Issue 3 (9th July 2015) - Ang, Marcus; Lim, Fiona; Htoon, Hla M; Tan, Donald; Mehta, Jodhbir S
Abstract : Purpose: To describe improvements in visual acuity and contrast sensitivity following Descemet stripping automated endothelial keratoplasty (DSAEK). Methods: We analysed 128 consecutive patients (128 eyes) with Fuchs endothelial dystrophy (FED) and bullous keratopathy (BK) who underwent DSAEK at a single tertiary referral centre from January 2006 to September 2009. Our main outcome measures were best-corrected visual acuity (BCVA) and contrast sensitivity over 24 months follow-up. Results: Median age was 67 (60–73) years with 55% women (n=70) and majority Chinese (74%, n=94) in our Asian population. There were no significant differences between demographics between the FED (48%, 61 eyes) and BK (52%, 67 eyes) groups. Forward multivariate linear regression adjusted for age, gender, donor graft thickness and diagnosis (FED vs BK) revealed that preoperative visual acuity was the most significant factor associated with visual acuity at 1 year (B=0.032, p=0.03, R 2 =0.122). Visual recovery was longer in eyes with BK, with a significantly better visual acuity in the FED group at 12 months (mean logarithm of the minimum angle of resolution BCVA BK: 0.27±0.1 vs FED: 0.22±0.9; p=0.001), but not significant at 24 months (p=0.154). Contrast sensitivity significantly improved more in the first 6 months in the FED when compared with the BK group (at 3.0, 6.0 and 12.0 cycles per degree, p<0.01). Conclusions: Our study suggests that while there was significant improvement in contrast sensitivity and visual acuity after DSAEK, poor preoperative visual acuity was associated with an inferior visual outcome and the time to recovery was longer in eyes with BK.